Book Review: Christel Gärtner, Linda Hennig & Olaf Müller (eds): Families and Religion: Dynamics of Transmission across Generations. 2025. - Martikainen, Tuomas (Finland, 2026)
Families and Religion: Dynamics of Transmission across Generations is an anthology focusing on the generational transmission of religion in Canada, Finland, Germany, Hungary, and Italy. The selected countries represent Western and post-Communist countries with either a Catholic or Protestant Christian majority, or mixed as in Canada and Germany. The editorial team of Christel Gärtner, Linda Hennig, and Olaf Müller is based at the University of Münster in Germany. The other main national contributors are established scholars in the sociology of religion. The book is based on a research project funded by the John Templeton Foundation.